Pendampingan belajar Matematika dan Fisika berbasis eksperimen di Dusun Malangrejo dan Temanggal II - Albertus Hariwangsa Panuluh; Maria Suci Apriani; Dwi Nugraheni Rositawati; Elisabeth Dian Atmajati; Veronika Fitri Rianasari (Abdimas Altruis: Jurnal Pengabdian kepada Masyarakat, 2026)
We conducted a community learning program on Mathematics and Physics tutoring based on simple experiments in Dusun Malangrejo and Dusun Temanggal II, Sleman Regency, Yogyakarta. The activities applied a participatory, collaborative, and experiment-based approach designed to be structured and highly interactive, to improve primary school students’ interest, understanding, and learning motivation in Mathematics and Physics. The program was implemented by a multidisciplinary team of lecturers and student volunteers from the Physics Education and Mathematics Education programs. The tutoring sessions were carried out from February to May 2025 in both locations. During the implementation, students were invited to engage in simple, safe experiments aligned with their grade level, followed by short discussions to connect the activities with concepts taught at school. Attendance records showed an average of seven participants per meeting in Malangrejo and 14 participants in Temanggal II. Based on field observations and informal feedback, students showed higher enthusiasm during hands-on sessions and reported that science and mathematics lessons felt more relatable and easier to understand after joining the program.